The Mathematics Algorithms Gaps from Students Perspectives: A Case of Selected Community Secondary Schools - Banele, Shima Dawson (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
The mixed case study research involved 120 students from community secondary schools located at Chanika Ward in Dar es Salaam were selected using non-probability approach deployed purposively technique. Objectively the study intended to determine and examine the school based contextual practices leading gaps in attainability of mathematics algorithms from students’ perspectives. Data were collected using four ranked Likert scale questionnaire and FGD thereafter analysed using Ms Excel and thematic content. The findings showed that students were experiencing mathematics algorithms gaps in 22 concepts supposed to be covered in the syllabus from form one to four; the identified classroom contextual gaps were categorized into ICT resources, pedagogical and students aspects. Recommendations were made for stakeholders to support schools, teachers and students with the digital and technological tools, creating supportive learning environments fostering creativity, collaboration, critical thinking and problem-solving skills built within Mathematics concepts algorithms fore-fronting the 4IR practices.